2016
DOI: 10.1016/j.bcmd.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

EPO-dependent induction of erythroferrone drives hepcidin suppression and systematic iron absorption under phenylhydrazine-induced hemolytic anemia

Abstract: a b s t r a c t a r t i c l e i n f oHemolytic anemia is a common form of anemia due to hemolysis, resulting in disordered iron homeostasis. In this study, a dose of 40 mg/kg phenylhydrazine (PHZ) was injected into mice to successfully establish a pronounced anemia animal model, which resulted in stress erythropoiesis and iron absorption. We found that serum erythropoietin (EPO) concentration was dramatically elevated by nearly 5000-fold for the first 2 days, and then drop to the basal level on day 6 after PHZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 26 publications
2
33
2
1
Order By: Relevance
“…This study raises questions about this new erythroid hormone and its role in hepcidin suppression in different types of anemia. [10][11][12][13] As there have been no previous reports on the relation between human serum erythroferrone and iron status parameters levels in cases with iron deficiency anemia; the present study aimed to demonstrate the relation between serum erythroferrone and iron status parameters levels in this widespread type of pediatric anemia.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This study raises questions about this new erythroid hormone and its role in hepcidin suppression in different types of anemia. [10][11][12][13] As there have been no previous reports on the relation between human serum erythroferrone and iron status parameters levels in cases with iron deficiency anemia; the present study aimed to demonstrate the relation between serum erythroferrone and iron status parameters levels in this widespread type of pediatric anemia.…”
Section: Discussionmentioning
confidence: 92%
“…Erythroferrone is lately identified by Kautz et al as key regulator of iron homeostasis during stress erythropoiesis by suppressing hepcidin expression. This study raises questions about this new erythroid hormone and its role in hepcidin suppression in different types of anemia …”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Jiang et al [8] demonstrated upregulation of erythroferrone in a mouse model of acute haemolytic anaemia. These studies suggest that in EPO-elevated states iron absorption is encouraged via erythroferrone regulation of hepcidin.…”
Section: Discussionmentioning
confidence: 99%
“…Erythroferrone secretion by erythroid precursors is stimulated by elevated EPO levels, and erythroferrone inhibits the secretion of hepcidin -resulting in a negative regulation of hepcidin by EPO. EPO is elevated in conditions that require increased production of RBC, such as after hemorrhage or in anemia, resulting in increased erythroferrone and finally in suppression of hepcidin (Kautz et al, 2015;Kim & Nemeth, 2015;Jiang et al, 2016), allowing iron to be mobilized from the liver and spleen to the plasma, and also increasing dietary iron absorption. This provides the required increased levels of iron for increased RBC production.…”
Section: Introductionmentioning
confidence: 99%